Socio-cultural relationship between recreational sea anglers and blue sharks (Prionace glauca) in the United Kingdom - Gemma L., Scotts (2023)
The blue shark (Prionace glauca) is commonly caught by recreational anglers around the United Kingdom (UK) – part of a population (North Atlantic) which has sustained declines of > 50% over the last three generations (36 years). Therefore, mitigating any detrimental impacts recreational fisheries might have on this species is crucial. This requires understanding anglers’ perceptions and behaviours, to co-design appropriate management measures. Here, we explore the socio-cultural relationship between anglers and blue sharks in the UK through structured surveys. A total of seven business operators and 44 recreational anglers responded throughout Aug-Nov 2021. Respondents primarily comprised of over-fifty, educated and wealthy male anglers. A positive relationship was identified: 100% of anglers have respect for sharks; 80% (n = 42) would like their fishing to inform research. We also found that socio-demographic variables correlate with certain perceptions, e.g., education level and political leanings were associated with the level of agreement to the statement “sharks are there for my enjoyment to catch” and “I want to catch the biggest shark possible”, respectively. Operators follow best fishing practices to minimise stress to sharks and 100% of operators wanted to contribute to research. Currently 43% (n = 3) submit catch data and one operator tags sharks. This willingness to contribute to research could improve our understanding of blue shark population structure, habitat use, and post-release mortality rates associated with recreational angling. This will not only help sustain shark stocks but also engage anglers in understanding the threats to sharks and benefit recreational fisheries that rely on stable shark populations.